Process for making a durable antibacterial fabric

CN122879976APending Publication Date: 2026-10-09FORMOSA TAFFETA (ZHONG SHAN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611186489.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]基于现有技术中抗菌剂仅靠物理吸附易洗脱脱落、而采用共价键接枝又容易因强反应条件而损伤纤维并破坏抗菌剂活性的问题,本发明的目的在于提供一种持久抗菌面料的制作工艺,通过面料表面接枝β环糊精与含金刚烷基+末端羟乙基的季铵盐进行包合、再经低温硅烷共价交联,得到高洗涤耐久性抗菌面料

Benefits of technology

1、本发明创新性地采用物理与化学协同将抗菌剂锚定在面料中,β-环糊精(β-CD)共价接枝于纤维表面,Ad-QAS借助金刚烷基与β-CD疏水空腔的高亲和主客体包合实现物理定位,使其杀菌用的季铵阳离子外露且不易随水流随机脱附,同时Ad-QAS末端羟乙基可与纤维/CD残余羟基经低温偶联剂发生共价键合,实现物理包合、化学键合的双重固定模式,使得抗菌剂在温和无强碱条件下被牢固固定,避免了传统接枝对纤维强度和抗菌剂活性的损伤,洗涤50次后抑菌率仍>96%,且抗菌剂保持率达90%左右,实现了高持久性、高安全性与加工友好性的统一。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a manufacturing process of a durable antibacterial fabric and belongs to the technical field of fabric preparation. First, the fabric is activated in a treatment liquid, then beta-cyclodextrin, a crosslinking agent, a catalyst and a penetrating agent I are mixed in deionized water I to obtain a padding liquid, the activated fabric is padded in the padding liquid, and beta-cyclodextrin grafted fabric is obtained after drying, then adamantyl quaternary ammonium salt and deionized water II are mixed, a clathration liquid is obtained after pH adjustment, the beta-cyclodextrin grafted fabric is immersed in the clathration liquid under light-proof conditions, and clathration loaded fabric is obtained after padding and drying, finally, a coupling agent solution is sprayed on the surface of the clathration loaded fabric, and a durable antibacterial fabric is obtained after solidification. The fabric provided by the application can maintain an antibacterial rate of more than 96% after 50 times of washing, and the antibacterial agent retention rate is about 90%, and the fabric has high antibacterial capacity, high durability and high safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fabric preparation technology, specifically to a manufacturing process for a durable antibacterial fabric. Background Technology

[0002] With increasing public awareness of health and higher demands for quality of life, the demand for antibacterial textiles is growing in fields such as medical, home, sports, and special functional clothing. These products effectively inhibit the attachment and reproduction of bacteria, fungi, and other microorganisms by introducing antibacterial active ingredients into the fabric, thereby reducing problems such as odor, skin infections, and cross-contamination at the source. They are widely used in surgical gowns, medical dressings, underwear, socks, sportswear, and hotel home textiles.

[0003] However, existing antibacterial fabric technologies generally suffer from a core contradiction: achieving a balance between antibacterial durability and safety / durability is difficult. Taking silver ion antibacterial agents as an example, while they have a broad antibacterial spectrum and high efficiency, free silver ions continuously dissolve and are lost during repeated washing. This not only leads to a rapid decline in antibacterial activity but also poses a potential risk of bioaccumulation after absorption by the human body. Furthermore, the dark deposits of silver ions can affect the appearance of the fabric. Quaternary ammonium salt antibacterial agents, although having a clear bactericidal mechanism and controllable cost, require high-temperature baking in traditional covalent grafting processes. Most quaternary ammonium salt molecules are prone to Hoffmann elimination or thermal decomposition at high temperatures, leading to decreased antibacterial activity and even the production of irritating byproducts. If physical adsorption is used for loading, the wash resistance is extremely poor, typically dropping below 50% after only a dozen or so standard washes. Natural essential oil microcapsule technology relies on the integrity of the capsule wall; wear or washing can cause the capsule to rupture, resulting in the complete release of antibacterial components, failing to achieve a lasting effect. In addition, most of the above technologies adopt a single anchoring mechanism—either relying on the rigid fixation of chemical bonds (washable but non-renewable) or the weak interaction of physical adsorption (slow-release but easily lost). The limitations of this single mechanism lead to a common dilemma faced by antibacterial fabrics in actual use: the initial antibacterial effect may be too strong, which may irritate the skin or accelerate the development of bacterial resistance. In the later stage, the antibacterial ingredients are exhausted and cannot be restored. The overall service life and cost performance of the product are far lower than consumers' expectations.

[0004] Given the various shortcomings of existing technologies, it is essential to propose a new manufacturing process for durable antibacterial fabrics. Summary of the Invention

[0005] Addressing the problems in existing technologies where antibacterial agents relying solely on physical adsorption are easily washed away, and where covalent grafting can damage fibers and destroy antibacterial activity due to strong reaction conditions, the present invention aims to provide a manufacturing process for durable antibacterial fabrics by grafting β-type antibacterial agents onto the fabric surface. Cyclodextrin is encapsulated with a quaternary ammonium salt containing adamantyl alkyl and terminal hydroxyethyl groups, and then covalently crosslinked with silane at low temperature to obtain a highly washable and durable antibacterial fabric.

[0006] The present invention provides a manufacturing process for a durable antibacterial fabric, comprising the following steps: S1: Activate the fabric by placing it in the treatment solution; S2: Mix β-cyclodextrin, crosslinking agent, catalyst and penetrant I in deionized water I to obtain padding solution. Place the fabric activated by S1 into the padding solution and pad it. After drying, obtain β-cyclodextrin grafted fabric. S3: Mix adamantyl quaternary ammonium salt and deionized water II, and adjust the pH to obtain an inclusion solution; S4: Under light-protected conditions, the β-cyclodextrin-grafted fabric is immersed in the inclusion solution, and then rolled and dried to obtain the inclusion-loaded fabric. S5: Spray a coupling agent solution onto the surface of the wrapped load fabric and cure it to obtain a durable antibacterial fabric; The adamantyl quaternary ammonium salt is 1-adamantanemethyl-dimethyl-(2-hydroxyethyl)ammonium chloride.

[0007] In some embodiments, 1-adamantanemethyl-dimethyl-(2-hydroxyethyl)ammonium chloride is prepared by the following steps: (1) 1-Chloromethyladamantane, N-methylethanolamine and an acid-binding agent are mixed in solvent I and reacted. After the reaction, the mixture is cooled and impurities are removed to obtain adamantane methylhydroxyethyl methylamine. (2) Adamantane methyl hydroxyethyl methylamine and iodomethane were mixed in solvent II and reacted. After the reaction, the solvent was evaporated to obtain crude quaternary ammonium iodide. (3) The crude quaternary ammonium iodide salt was dissolved in a mixed solution, and after purification and drying, 1-adamantanemethyl-dimethyl-(2-hydroxyethyl)ammonium chloride was obtained.

[0008] It should be noted that this invention achieves the assembly of adamantyl, quaternary ammonium salt antibacterial center, and hydroxyethyl reaction tail in a stepwise manner to obtain 1-adamantanemethyl-dimethyl-(2-hydroxyethyl)ammonium chloride Ad-QAS. First, 1-chloromethyladamantane is used as an electrophile. The methylene carbon in its adamantanemethyl chloride structure has high electrophilic activity. The secondary amine nitrogen atom of N-methylethanolamine (MMEA) attacks the methylene carbon with a lone pair of electrons, resulting in a nucleophilic substitution reaction. At the same time, an acid-binding agent neutralizes the generated hydrogen chloride to prevent the protonation and deactivation of MMEA, yielding a tertiary amine intermediate. The nitrogen atom of the above tertiary amine intermediate undergoes a second substitution reaction with iodomethane. The methyl carbon is attacked by the amine nitrogen to form a quaternary ammonium positive center, yielding crude iodide quaternary ammonium salt. Finally, iodide ions are removed by column chromatography with an exchange resin to obtain the final product.

[0009] In some embodiments, the treatment solution is a mixture of sodium hydroxide, penetrant II and water in a ratio of 20-30g:1g:0.8-1.2L; the ratio of β-cyclodextrin, crosslinking agent, catalyst, penetrant I and deionized water I is 60-80g:50-70g:20-25g:1g:780-820mL.

[0010] In some embodiments, the crosslinking agent is selected from at least one of butanetetracarboxylic acid and citric acid; the catalyst is selected from at least one of sodium hypophosphite, sodium dihydrogen phosphate, and disodium hydrogen phosphate; and the penetrant I and penetrant II are fatty alcohol polyoxyethylene ether or lauryl alcohol polyoxyethylene ether-9.

[0011] In some embodiments, the ratio of adamantyl quaternary ammonium salt to deionized water II is 5-10 g: 0.8-1.2 L.

[0012] In some embodiments, the coupling agent solution is prepared by the following steps: first, (3-glycidyl etheroxypropyl)trimethoxysilane, anhydrous ethanol and deionized water are mixed in a ratio of 0.3-0.5g:75-85mL:15-25mL, and then the pH is adjusted to 4-5 for hydrolysis.

[0013] In some embodiments, the molar ratio of 1-chloromethyladamantane, N-methylethanolamine and the acid-binding agent is 1:1.2-1.5:1.2-2; the acid-binding agent is selected from at least one of anhydrous potassium carbonate, triethylamine, and diisopropylethylamine.

[0014] In some embodiments, the mass of solvent I is 5-8 times the sum of the masses of 1-chloromethyladamantane, N-methylethanolamine and the acid-binding agent; solvent I is selected from at least one of anhydrous tetrahydrofuran and dimethylformamide.

[0015] In some embodiments, the molar ratio of adamantane methyl hydroxyethyl methylamine to iodomethane is 1:1.2-1.5; solvent II is selected from at least one of anhydrous acetonitrile and acetone; and the mass of solvent II is 3.3-5 times the mass of adamantane methyl hydroxyethyl methylamine.

[0016] In some embodiments, in step (1), the reaction is carried out under inert gas protection and refluxed for 6-8 hours; in step (2), the reaction is carried out under inert gas protection and at 30-40°C for 4-6 hours.

[0017] In this invention, the surface of the fabric fibers must contain a sufficient density of reactive hydroxyl groups (or amino groups) in order to covalently graft β-cyclodextrin onto them, including but not limited to cotton and linen fabrics (flax, ramie, jute, hemp), and cellulose fibers (natural / regenerated cellulose fibers).

[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention innovatively employs a combination of physical and chemical methods to anchor antibacterial agents in fabrics. β-cyclodextrin (β-CD) is covalently grafted onto the fiber surface, and Ad-QAS achieves physical positioning through the high affinity host-guest encapsulation of the adamantyl alkyl group with the hydrophobic cavity of β-CD. This exposes the bactericidal quaternary ammonium cations and prevents them from randomly desorbing with water flow. Simultaneously, the terminal hydroxyethyl group of Ad-QAS can covalently bond with the residual hydroxyl groups of the fiber / CD via a low-temperature coupling agent, achieving a dual fixation mode of physical encapsulation and chemical bonding. This ensures that the antibacterial agent is firmly fixed under mild, non-alkaline conditions, avoiding the damage to fiber strength and antibacterial agent activity caused by traditional grafting. After 50 washes, the antibacterial rate is still >96%, and the antibacterial agent retention rate reaches about 90%, achieving a balance between high durability, high safety, and processing friendliness.

[0019] 2. The Ad-QAS provided by this invention consists of an adamantyl group, a quaternary ammonium salt antibacterial center, and a hydroxyethyl reactive tail. The adamantyl group head serves as a hydrophobic anchoring end, utilizing the spatial complementarity between the adamantyl backbone and the hydrophobic cavity of β-cyclodextrin to achieve physical locking through host-guest inclusion. The adamantyl-β-cyclodextrin exhibits strong affinity supramolecular interaction, providing stable physical anchoring force under conventional washing conditions. The quaternary ammonium salt body serves as the antibacterial active center; the dimethyl-substituted quaternary ammonium positive charge disrupts the bacterial cell membrane structure through electrostatic interaction, exhibiting contact bactericidal effects against both Gram-positive and Gram-negative bacteria. The hydroxyethyl tail serves as the chemical reactive end; its primary alcohol hydroxyl group has significantly higher reactivity than the secondary alcohol hydroxyl group of β-cyclodextrin, and under low-temperature conditions, it preferentially undergoes esterification with fibers or crosslinking agents, forming a covalent chemical lock. This three-segment configuration enables a single molecule to simultaneously possess three functions: physical inclusion, biological activity, and chemical reactivity. It retains the original antibacterial activity and low dissolution characteristics of quaternary ammonium salts, while also possessing an active anchoring function, thereby achieving high wash durability of the fabric.

[0020] 3. Traditional polycarboxylic acid crosslinking systems require high-temperature baking at 160-180℃ to effectively form esters. However, most quaternary ammonium salts undergo Hoffmann elimination reactions or thermal decomposition at this temperature, resulting in the loss of antibacterial activity. This invention addresses the β-hydrogen content of Ad-QAS molecules by designing a low-temperature curing route. It utilizes (3-glycidyl etheroxypropyl)trimethoxysilane (GPTMS) as a coupling agent, leveraging its epoxy groups to undergo ring-opening etherification with hydroxyethyl groups at 80-100℃, while simultaneously dehydrating and condensing the silanol with the cellulose hydroxyl groups, thus avoiding the risks associated with high temperatures.

[0021] 4. The antibacterial fabric process provided by this invention is not limited to a single fabric. Any fiber substrate rich in accessible hydroxyl groups can be selected according to actual needs. Any cellulosic fiber with a similar hydroxyl density, including hemp (flax, ramie, hemp) and regenerated cellulose (viscose, modal, lyocell, bamboo pulp fiber), can be directly applied to this scheme. Only the alkali activation intensity needs to be adjusted to avoid excessive damage. For synthetic fibers (polyester, nylon), although they lack hydroxyl groups themselves, hydroxyl groups can be introduced through alkali reduction, plasma treatment, or cellulose undercoating pretreatment, thus making them indirectly applicable. This substrate adaptability allows this scheme to break through the limitation of a single fiber and is applicable to a variety of fabrics.

[0022] 5. This scheme avoids the use of heavy metals (silver, copper, and zinc ions) and persistent organic pollutants (triclosan and halogenated phenols) from molecular design to process aids. Ad-QAS is a fully organic small molecule with a well-defined biodegradation pathway; β-cyclodextrin is a natural starch derivative that is biodegradable; crosslinking agents and catalysts can be removed by washing; and the GPTMS route is completely phosphorus-free, exhibiting high environmental safety. Detailed Implementation

[0023] The present invention will now be described in further detail with reference to specific embodiments.

[0024] Example 1 A manufacturing process for a durable antibacterial fabric includes the following steps: S1: Place the fabric in the treatment solution and treat it at 98°C for 40 minutes; wherein, the treatment solution is a mixture of sodium hydroxide, fatty alcohol polyoxyethylene ether and water in a ratio of 25g:1g:1L. S2: Mix β-cyclodextrin, butanetetracarboxylic acid, sodium hypophosphite and fatty alcohol polyoxyethylene ether in deionized water I in a ratio of 70g:60g:23g:1g:800mL to obtain padding solution. Place the fabric activated by S1 into the padding solution. After sufficient impregnation, pressurize the rollers to remove excess liquid. Control the roll residue at 85%. Dry at 85℃ for 2min to obtain β-cyclodextrin grafted fabric. S3: Mix adamantyl quaternary ammonium salt and deionized water II at a ratio of 8 g: 1 L, and adjust the pH to 6.5 to obtain the inclusion solution; S4: Under light-protected conditions, the β-cyclodextrin-grafted fabric was immersed in a binding solution at 35°C for 1.8 hours. After sufficient immersion, the excess liquid was removed by applying pressure with rollers. The fabric was then taken out and dried at 85°C for 7 minutes to obtain the bound load fabric. S5: Spray the coupling agent solution onto the surface of the encapsulated and loaded fabric, and dry and cure it at 90°C for 7 minutes to obtain a durable antibacterial fabric; wherein, the coupling agent solution is prepared by the following steps: first, it is prepared by mixing (3-glycidyl ether oxypropyl)trimethoxysilane, anhydrous ethanol and deionized water in a ratio of 0.4g:80mL:20mL, and then adjusting the pH to 4 for hydrolysis.

[0025] The adamantyl quaternary ammonium salt is 1-adamantanemethyl-dimethyl-(2-hydroxyethyl)ammonium chloride, which is prepared by the following steps: (1) 1-Chloromethyladamantane, N-methylethanolamine and anhydrous potassium carbonate in a molar ratio of 1:1.3:1.6 were mixed in anhydrous tetrahydrofuran and refluxed under an inert gas protection for 7 h. After the reaction, the mixture was cooled and impurities were removed to obtain adamantane methylhydroxyethyl methylamine. The mass of anhydrous tetrahydrofuran was 6 times the sum of the masses of 1-chloromethyladamantane, N-methylethanolamine and acid-binding agent. (2) Adamantane methyl hydroxyethyl methylamine and iodomethane in a molar ratio of 1:1.3 were mixed in anhydrous acetonitrile and reacted at 35°C for 5 h under inert gas protection. After the reaction, the solvent was removed by evaporation to obtain crude quaternary ammonium iodide. The mass of anhydrous acetonitrile was 4 times that of adamantane methyl hydroxyethyl methylamine. (3) Dissolve the crude quaternary ammonium iodide salt in a minimum volume of 50% ethanol aqueous solution (minimum volume refers to the minimum amount of ethanol aqueous solution that just completely dissolves the iodide salt), and then pass it through a Dowex 1×8 Cl... - The fraction was obtained by column chromatography with anion exchange resin, eluted with deionized water, and freeze-dried to give 1-adamantanemethyl-dimethyl-(2-hydroxyethyl)ammonium chloride.

[0026] Example 2 A manufacturing process for a durable antibacterial fabric includes the following steps: S1: Place the fabric in the treatment solution and treat it at 100°C for 30 minutes; wherein, the treatment solution is a mixture of sodium hydroxide, lauryl alcohol polyoxyethylene ether-9 and water in a ratio of 30g:1g:1.2L. S2: Mix β-cyclodextrin, citric acid, sodium dihydrogen phosphate and lauryl alcohol polyoxyethylene ether-9 in deionized water I in a ratio of 80g:70g:25g:1g:820mL to obtain padding solution. Place the fabric activated by S1 into the padding solution and pad it. After sufficient impregnation, pressurize the rollers to remove excess liquid and control the padding rate at 90%. Dry at 90℃ for 2min to obtain β-cyclodextrin grafted fabric. S3: Mix adamantyl quaternary ammonium salt and deionized water II at a ratio of 10g:1.2L, and adjust the pH to 7.0 to obtain the inclusion solution; S4: Under light-protected conditions, the β-cyclodextrin-grafted fabric is immersed in a binding solution at 40°C for 1.5 hours. After sufficient immersion, the excess liquid is removed by applying pressure with rollers. The fabric is then taken out and dried at 90°C for 5 minutes to obtain the bound and loaded fabric. S5: Spray the coupling agent solution onto the surface of the wrapped and loaded fabric, and dry and cure it at 100°C for 5 minutes to obtain a durable antibacterial fabric; wherein, the coupling agent solution is prepared by the following steps: first, it is prepared by mixing (3-glycidyl ether oxypropyl)trimethoxysilane, anhydrous ethanol and deionized water in a ratio of 0.5g:75mL:25mL, and then adjusting the pH to 4-5 and hydrolyzing it to obtain the final product.

[0027] The adamantyl quaternary ammonium salt is 1-adamantanemethyl-dimethyl-(2-hydroxyethyl)ammonium chloride, which is prepared by the following steps: (1) 1-Chloromethyladamantane, N-methylethanolamine and triethylamine in a molar ratio of 1:1.5:2 were mixed in dimethylformamide and refluxed under inert gas protection for 8 hours. After the reaction, the mixture was cooled and impurities were removed to obtain adamantane methyl hydroxyethyl methylamine. The mass of dimethylformamide used was 8 times the sum of the masses of 1-chloromethyladamantane, N-methylethanolamine and acid-binding agent. (2) Adamantane methyl hydroxyethyl methylamine and iodomethane in a molar ratio of 1:1.5 were mixed in acetone and reacted at 40°C for 4 hours under inert gas protection. After the reaction, the solvent was evaporated to obtain crude quaternary ammonium iodide. The mass of acetone used was 5 times that of adamantane methyl hydroxyethyl methylamine. (3) Dissolve the crude quaternary ammonium iodide salt in a minimum volume of 50% ethanol aqueous solution (minimum volume refers to the minimum amount of ethanol aqueous solution that just completely dissolves the iodide salt), and then pass it through a Dowex 1×8 Cl... - The fraction was obtained by column chromatography with anion exchange resin, eluted with deionized water, and freeze-dried to give 1-adamantanemethyl-dimethyl-(2-hydroxyethyl)ammonium chloride.

[0028] Example 3 A manufacturing process for a durable antibacterial fabric includes the following steps: S1: Place the fabric in the treatment solution and treat it at 95°C for 45 minutes; wherein, the treatment solution is a mixture of sodium hydroxide, fatty alcohol polyoxyethylene ether and water in a ratio of 20g:1g:0.8L. S2: Mix β-cyclodextrin, butanetetracarboxylic acid, disodium hydrogen phosphate and fatty alcohol polyoxyethylene ether in deionized water I in a ratio of 60g:50g:20g:1g:780mL to obtain padding solution. Place the fabric activated by S1 into the padding solution and pad it. After sufficient impregnation, pressurize the rollers to remove excess liquid and control the roll residue at 80%. Dry at 80℃ for 3min to obtain β-cyclodextrin grafted fabric. S3: Mix adamantyl quaternary ammonium salt and deionized water II at a ratio of 5g:0.8L, and adjust the pH to 6.5 to obtain the inclusion solution; S4: Under light-protected conditions, the β-cyclodextrin-grafted fabric is immersed in a binding solution at 30°C for 1.5 hours. After sufficient immersion, the excess liquid is removed by applying pressure with rollers. The fabric is then taken out and dried at 80°C for 5 minutes to obtain the bound load fabric. S5: Spray the coupling agent solution onto the surface of the encapsulated and loaded fabric, and dry and cure it at 80°C for 5 minutes to obtain a durable antibacterial fabric; wherein, the coupling agent solution is prepared by the following steps: first, it is prepared by mixing (3-glycidyl ether oxypropyl)trimethoxysilane, anhydrous ethanol and deionized water in a ratio of 0.3g:75mL:15mL, and then adjusting the pH to 4 for hydrolysis.

[0029] The adamantyl quaternary ammonium salt is 1-adamantanemethyl-dimethyl-(2-hydroxyethyl)ammonium chloride, which is prepared by the following steps: (1) 1-Chloromethyladamantane, N-methylethanolamine and diisopropylethylamine in a molar ratio of 1:1.2:1.2 were mixed in dimethylformamide and refluxed under inert gas protection for 6 h. After the reaction, the mixture was cooled and impurities were removed to obtain adamantane methyl hydroxyethyl methylamine. The mass of dimethylformamide used was 5 times the sum of the masses of 1-chloromethyladamantane, N-methylethanolamine and acid-binding agent. (2) Adamantane methyl hydroxyethyl methylamine and iodomethane in a molar ratio of 1:1.2 were mixed in anhydrous acetonitrile and reacted at 30°C for 6 h under inert gas protection. After the reaction, the solvent was removed by evaporation to obtain crude quaternary ammonium iodide. The mass of anhydrous acetonitrile was 3.3 times that of adamantane methyl hydroxyethyl methylamine. (3) Dissolve the crude quaternary ammonium iodide salt in a minimum volume of 50% ethanol aqueous solution (minimum volume refers to the minimum amount of ethanol aqueous solution that just completely dissolves the iodide salt), and then pass it through a Dowex 1×8 Cl... - The fraction was obtained by column chromatography with anion exchange resin, eluted with deionized water, and freeze-dried to give 1-adamantanemethyl-dimethyl-(2-hydroxyethyl)ammonium chloride.

[0030] Example 4 A manufacturing process for a durable antibacterial fabric includes the following steps: S1: Place the fabric in the treatment solution and treat it at 96°C for 35 minutes; wherein, the treatment solution is a mixture of sodium hydroxide, lauryl alcohol polyoxyethylene ether-9 and water in a ratio of 22g:1g:0.9L. S2: Mix β-cyclodextrin, citric acid, sodium hypophosphite and lauryl alcohol polyoxyethylene ether-9 in deionized water I in a ratio of 65g:55g:21g:1g:790mL to obtain padding solution. Place the fabric activated by S1 into the padding solution and pad it. After sufficient impregnation, pressurize the rollers to remove excess liquid and control the roll residue at 82%. Dry at 82℃ for 3min to obtain β-cyclodextrin grafted fabric. S3: Mix adamantyl quaternary ammonium salt and deionized water II at a ratio of 6g:0.9L, and adjust the pH to 6.7 to obtain the inclusion solution; S4: Under light-protected conditions, the β-cyclodextrin-grafted fabric was immersed in a binding solution at 32°C for 1.7 hours. After sufficient immersion, the excess liquid was removed by applying pressure with rollers. The fabric was then taken out and dried at 82°C for 6 minutes to obtain the bound and loaded fabric. S5: Spray the coupling agent solution onto the surface of the encapsulated and loaded fabric, and dry and cure it at 85°C for 6 minutes to obtain a durable antibacterial fabric; wherein, the coupling agent solution is prepared by the following steps: first, it is prepared by mixing (3-glycidyl ether oxypropyl)trimethoxysilane, anhydrous ethanol and deionized water in a ratio of 0.4g:78mL:17mL, and then adjusting the pH to 4 for hydrolysis.

[0031] The adamantyl quaternary ammonium salt is 1-adamantanemethyl-dimethyl-(2-hydroxyethyl)ammonium chloride, which is prepared by the following steps: (1) 1-Chloromethyladamantane, N-methylethanolamine and triethylamine in a molar ratio of 1:1.3:1.4 were mixed in anhydrous tetrahydrofuran and refluxed under an inert gas protection for 7 h. After the reaction, the mixture was cooled and impurities were removed to obtain adamantanemethylhydroxyethylmethylamine. The mass of anhydrous tetrahydrofuran was 6 times the sum of the masses of 1-chloromethyladamantane, N-methylethanolamine and acid-binding agent. (2) Adamantane methyl hydroxyethyl methylamine and iodomethane in a molar ratio of 1:1.3 were mixed in anhydrous acetonitrile and reacted at 35°C for 5 h under inert gas protection. After the reaction, the solvent was removed by evaporation to obtain crude quaternary ammonium iodide. The mass of anhydrous acetonitrile was 3.8 times that of adamantane methyl hydroxyethyl methylamine. (3) Dissolve the crude quaternary ammonium iodide salt in a minimum volume of 50% ethanol aqueous solution (minimum volume refers to the minimum amount of ethanol aqueous solution that just completely dissolves the iodide salt), and then pass it through a Dowex 1×8 Cl... - The fraction was obtained by column chromatography with anion exchange resin, eluted with deionized water, and freeze-dried to give 1-adamantanemethyl-dimethyl-(2-hydroxyethyl)ammonium chloride.

[0032] Example 5 A manufacturing process for a durable antibacterial fabric includes the following steps: S1: Place the fabric in the treatment solution and treat it at 98°C for 42 minutes; wherein, the treatment solution is a mixture of sodium hydroxide, fatty alcohol polyoxyethylene ether and water in a ratio of 28g:1g:1.1L. S2: β-cyclodextrin, butanetetracarboxylic acid, disodium hydrogen phosphate and lauryl alcohol polyoxyethylene ether-9 are mixed in deionized water I in a ratio of 75g:65g:24g:1g:810mL to obtain a padding solution. The fabric activated by S1 is placed in the padding solution and padded. After sufficient impregnation, the rolls are pressed to remove excess liquid. The padding rate is controlled at 88%. The fabric is dried at 85℃ for 3min to obtain β-cyclodextrin grafted fabric. S3: Mix adamantyl quaternary ammonium salt and deionized water II at a ratio of 9 g: 1.1 L, and adjust the pH to 7.0 to obtain the inclusion solution; S4: Under light-protected conditions, the β-cyclodextrin-grafted fabric was immersed in a binding solution at 38°C for 1.8 hours. After sufficient immersion, the excess liquid was removed by applying pressure with rollers. The fabric was then taken out and dried at 88°C for 7 minutes to obtain the bound and loaded fabric. S5: Spray the coupling agent solution onto the surface of the encapsulated and loaded fabric, and dry and cure it at 95°C for 7 minutes to obtain a durable antibacterial fabric; wherein, the coupling agent solution is prepared by the following steps: first, it is prepared by mixing (3-glycidyl ether oxypropyl)trimethoxysilane, anhydrous ethanol and deionized water in a ratio of 0.4g:82mL:23mL, and then adjusting the pH to 5 and hydrolyzing it to obtain the final product.

[0033] The adamantyl quaternary ammonium salt is 1-adamantanemethyl-dimethyl-(2-hydroxyethyl)ammonium chloride, which is prepared by the following steps: (1) 1-Chloromethyladamantane, N-methylethanolamine and diisopropylethylamine in a molar ratio of 1:1.4:1.8 were mixed in dimethylformamide and refluxed under inert gas protection for 8 hours. After the reaction, the mixture was cooled and impurities were removed to obtain adamantane methyl hydroxyethyl methylamine. The mass of dimethylformamide was 7 times the sum of the masses of 1-chloromethyladamantane, N-methylethanolamine and acid-binding agent. (2) Adamantane methyl hydroxyethyl methylamine and iodomethane in a molar ratio of 1:1.4 were mixed in acetone and reacted at 38°C for 5.5 h under inert gas protection. After the reaction, the solvent was removed by evaporation to obtain crude quaternary ammonium iodide. The mass of acetone used was 4.5 times that of adamantane methyl hydroxyethyl methylamine. (3) Dissolve the crude quaternary ammonium iodide salt in a minimum volume of 50% ethanol aqueous solution (minimum volume refers to the minimum amount of ethanol aqueous solution that just completely dissolves the iodide salt), and then pass it through a Dowex 1×8 Cl... - The fraction was obtained by column chromatography with anion exchange resin, eluted with deionized water, and freeze-dried to give 1-adamantanemethyl-dimethyl-(2-hydroxyethyl)ammonium chloride.

[0034] Comparative Example 1 It is basically the same as Example 1, except that the fabric is not grafted with β-cyclodextrin, that is, step S2 is omitted.

[0035] Comparative Example 2 This is basically the same as Example 1, except that the adamantyl quaternary ammonium salt is replaced with a traditional quaternary ammonium salt antibacterial agent (hexadecyltrimethylammonium chloride CTAC).

[0036] Comparative Example 3 It is basically the same as Example 1, except that the coupling agent solution is not sprayed on the fabric surface, that is, step S5 is omitted.

[0037] Comparative Example 4 It is basically the same as Example 1, except that 1-chloromethyladamantane in step (1) of adamantyl quaternary ammonium salt preparation is replaced with 1-chloro-n-dodecane, that is, adamantyl is missing.

[0038] Comparative Example 5 The process is basically the same as in Example 1, except that N-methylethanolamine in step (1) of the preparation of adamantyl quaternary ammonium salt is replaced with N,N-dimethylmethylamine, i.e., the hydroxyethyl tail is missing.

[0039] Comparative Example 6 It is basically the same as Example 1, except that the step (2) of preparing adamantyl quaternary ammonium salt is omitted, that is, the antibacterial center of quaternary ammonium salt is missing.

[0040] The fabrics prepared in Examples 1-5 and Comparative Examples 1-5 were subjected to performance tests, and the test results are shown in Table 1.

[0041] The antibacterial properties were determined according to standard GB / T 20944.3-2008 "Evaluation of Antibacterial Properties of Textiles - Part 3: Shaking Method", with Staphylococcus aureus ATCC 6538 and Escherichia coli ATCC 25922 as inoculum concentrations of ~10. 5 CFU / mL, after 18-24 hours of contact, the inhibition rate = (number of colonies in the blank control) Sample colony count / Blank control colony count × 100%.

[0042] Durable antibacterial properties: Referring to the standard GB / T 8629-2017 "Home washing and drying procedures for textile testing", program 4N (40℃, standard detergent ECE, liquor ratio 1:30) was used. After each wash, the product was air-dried at room temperature, and the antibacterial rate was tested after 30 and 50 washes.

[0043] Antimicrobial agent fixation amount: The UV-Vis extraction quantitative method was used to quantify the Ad-QAS extracted from the fabric after 50 washes, and the antimicrobial agent load per unit mass of fabric was calculated.

[0044] Fiber breaking strength retention rate: Refer to standard GB / T 3923.1-2013 "Textiles - Tensile Properties of Fabrics - Part 1: Determination of Breaking Strength and Elongation at Break (Strip Method)", with a clamping distance of 200 mm, a tensile speed of 100 mm / min, and 5 measurements in each of the warp and weft directions, and the average value is taken. Breaking strength retention rate = (breaking strength after finishing / breaking strength of the original fabric) × 100%. The breaking strength of the original fabric is 470 N (typical plain weave cotton).

[0045] Table 1

[0046] As can be seen from Table 1, the fabrics provided in Examples 1-5 of the present invention have excellent antibacterial properties, with an antibacterial rate of over 96.0% after 50 washes, which is significantly better than any comparative example. After 50 washes, the antibacterial agent fixation rate remains at around 90%. The physical host-guest encapsulation and chemical bonding enable the antibacterial agent to effectively and firmly adhere to the fabric. In addition, the fabric strength retention rate provided in the embodiments of the present invention is also over 90%, indicating that the process adopted in this solution causes less fiber loss and the fabric still has good tensile strength.

[0047] As can be seen from the comparative examples, in Comparative Example 1 without β-CD grafting, Ad-QAS reacts with the fiber solely through the reaction of hydroxyethyl groups, resulting in low loading and uneven distribution. It quickly becomes ineffective against both types of bacteria, and the antibacterial rate decreases significantly. However, the strength retention rate is relatively high because the padding and baking steps are skipped, minimizing fiber damage. Comparative Example 2 uses CTAC, which has the worst antibacterial performance. Traditional quaternary ammonium salts cannot be effectively anchored on β-CD grafted cotton, resulting in low fixation and near-ineffectiveness after 50 washes. Comparative Example 3, without the application of coupling agent solution, initially has a high retention rate of 99.4%, but drops to 38% after 50 washes. The host-guest inclusion complex alone can provide excellent initial loading and short-term sustained release. However, under the competition of surfactants and mechanical shearing during repeated washing, the adamantane-β-CD inclusion balance is continuously disturbed. Furthermore, due to the lack of the low-temperature coupling agent GPTMS, chemical bonding cannot occur, ultimately leading to significant loss. At the same time, there is no GPTMS crosslinking, so the fiber is not subjected to additional chemical lock damage, resulting in a high strength retention rate.

[0048] Comparative Example 4 lacks the adamantyl group, thus failing to form physical inclusion. Although the chemical bond can initially fix some molecules, it undergoes hydrolytic breakage in alkaline washing liquid, resulting in direct molecule loss. This leads to a significant decrease in both antibacterial rate and fixation rate after 50 washes. Comparative Example 5 lacks the hydroxyethyl tail, similar to Comparative Example 3. After 50 long-term washes, it is insufficient to maintain long-lasting antibacterial activity. The lack of chemical bond causes a decrease in both antibacterial rate and fixation rate. Comparative Example 6 lacks the quaternary ammonium salt antibacterial center. Its initial and post-wash antibacterial rates are both below 10%, close to those of blank cotton fabric, indicating that the antibacterial activity originates from the positive charge of quaternary ammonium, and the adamantyl group and hydroxyethyl group themselves do not possess bactericidal function.

[0049] The above descriptions are merely some embodiments of the present invention. Those skilled in the art can make various modifications and improvements without departing from the inventive concept of the present invention, and these all fall within the scope of protection of the present invention.

Claims

1. A manufacturing process for a durable antibacterial fabric, characterized in that, Includes the following steps: S1: Activate the fabric by placing it in the treatment solution; S2: Mix β-cyclodextrin, crosslinking agent, catalyst and penetrant I in deionized water I to obtain padding solution. Place the fabric activated by S1 into the padding solution and pad it. After drying, obtain β-cyclodextrin grafted fabric. S3: Mix adamantyl quaternary ammonium salt and deionized water II, and adjust the pH to obtain an inclusion solution; S4: Under light-protected conditions, the β-cyclodextrin grafted fabric is immersed in the inclusion solution, and then rolled and dried to obtain the inclusion-loaded fabric. S5: Spray a coupling agent solution onto the surface of the encapsulated load fabric and cure it to obtain a durable antibacterial fabric; The adamantyl quaternary ammonium salt is 1-adamantanemethyl-dimethyl-(2-hydroxyethyl)ammonium chloride.

2. The manufacturing process of the durable antibacterial fabric according to claim 1, characterized in that, The 1-adamantanemethyl-dimethyl-(2-hydroxyethyl)ammonium chloride was prepared by the following steps: (1) 1-Chloromethyladamantane, N-methylethanolamine and an acid-binding agent are mixed in solvent I and reacted. After the reaction, the mixture is cooled and impurities are removed to obtain adamantane methylhydroxyethyl methylamine. (2) The adamantane methyl hydroxyethyl methylamine and iodomethane are mixed in solvent II and reacted. After the reaction, the solvent is evaporated to obtain crude quaternary ammonium iodide. (3) The crude iodide quaternary ammonium salt was dissolved in a mixed solution, purified and dried to obtain 1-adamantanemethyl-dimethyl-(2-hydroxyethyl)ammonium chloride.

3. The manufacturing process of the durable antibacterial fabric according to claim 1, characterized in that, The treatment solution is composed of sodium hydroxide, penetrant II and water in a ratio of 20-30g:1g:0.8-1.2L; the ratio of β-cyclodextrin, crosslinking agent, catalyst, penetrant I and deionized water I is 60-80g:50-70g:20-25g:1g:780-820mL.

4. The manufacturing process of the durable antibacterial fabric according to claim 3, characterized in that, The crosslinking agent is selected from at least one of butanetetracarboxylic acid and citric acid; the catalyst is selected from at least one of sodium hypophosphite, sodium dihydrogen phosphate, and disodium hydrogen phosphate; the penetrant I and the penetrant II are fatty alcohol polyoxyethylene ether or lauryl alcohol polyoxyethylene ether-9.

5. The manufacturing process of the durable antibacterial fabric according to claim 1, characterized in that, The ratio of the adamantyl quaternary ammonium salt to the deionized water II is 5-10g:0.8-1.2L.

6. The manufacturing process of the durable antibacterial fabric according to claim 1, characterized in that, The coupling agent solution is prepared by the following steps: first, (3-glycidyl etheroxypropyl)trimethoxysilane, anhydrous ethanol and deionized water are mixed in a ratio of 0.3-0.5g:75-85mL:15-25mL, and then the pH is adjusted to 4-5 for hydrolysis.

7. The manufacturing process of the durable antibacterial fabric according to claim 2, characterized in that, The molar ratio of 1-chloromethyladamantane, N-methylethanolamine and the acid-binding agent is 1:1.2-1.5:1.2-2; the acid-binding agent is selected from at least one of anhydrous potassium carbonate, triethylamine and diisopropylethylamine.

8. The manufacturing process of the durable antibacterial fabric according to claim 7, characterized in that, The mass of solvent I is 5-8 times the sum of the masses of 1-chloromethyladamantane, N-methylethanolamine and the acid-binding agent; solvent I is selected from at least one of anhydrous tetrahydrofuran and dimethylformamide.

9. The manufacturing process of the durable antibacterial fabric according to claim 2, characterized in that, The molar ratio of adamantane methyl hydroxyethyl methylamine to iodomethane is 1:1.2-1.5; solvent II is selected from at least one of anhydrous acetonitrile and acetone; the mass of solvent II is 3.3-5 times the mass of adamantane methyl hydroxyethyl methylamine.

10. The manufacturing process of the durable antibacterial fabric according to claim 2, characterized in that, In step (1), the reaction is carried out under inert gas protection and refluxed for 6-8 hours; in step (2), the reaction is carried out under inert gas protection and at 30-40℃ for 4-6 hours.